A Third Option: Understanding and Assessing Non-binary Gender Policies in the United States. Issue 2 (2nd April 2020) - Elias, Nicole; Colvin, Roddrick
Abstract : Our fundamental understandings and treatments of gender and gender identity within the United States are evolving. Recently, a few countries and several U.S. states have moved away from the binary categories of male and female to include a non-binary gender option for official state documents. This third, gender-neutral option, is usually represented as "X" where "M" for male and "F" for female traditionally appeared. The purpose of this study is twofold; first, to utilize Iris Marion Young's theory of oppression to help contextualize the historical oppression of non-binary gender identity recognition by the State, and second, to analyze recent efforts by U.S. states to include non-binary gender categories. Using Young's theory for normative explanation along with the Open Society Foundations' (OSF) practical recommendations, we present a simple administrative framework for comparing proposed, adopted, and enacted non-binary gender policies across the United States. Tying each OSF best practice to one of Young's faces of oppression, we are able to assess each law or policies' effectiveness in dismantling the oppressive binary constructs of society.